A low-dust thermal insulation covering agent and preparation method thereof

By using low-dust cloth insulation covers in the metallurgy industry, and using the synergy of materials such as silicon sol, aluminum sol, etc., the problem of difficult control of the thickness and uniformity of traditional covers during the addition process is solved, and efficient and uniform insulation effect is achieved, which is suitable for modern metallurgical industry.

CN119177559BActive Publication Date: 2025-03-14LENGSHUIJIANG GAOKE KILN REFRACTORY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411698869.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-14
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

During the addition of existing insulation covering agents, it is difficult to control the thickness and uniformity of the covering agent, resulting in insufficient insulation effect in some areas, and traditional powdered covering agents are not suitable for the needs of the modern metallurgical industry.

Method used

A low-dust cloth-shaped insulation covering agent is used to prepare a reusable ceramic fiber cloth covering agent through the synergy of silicon sol, aluminum sol, calcium chloride, magnesium chloride, expanded vermiculite powder, fluorite powder and high-temperature phase-changing non-Newtonian materials to ensure uniformity and efficiency.

Benefits of technology

The uniform addition of insulation cover agents and efficient heat insulation are achieved, which significantly improves the coverage effect and uniformity in metallurgical processes, and also has the advantages of environmentally friendly materials, seamless gap filling and multiple functions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention belongs to the technical field of steel smelting insulation, and specifically relates to a low-dust insulation covering agent and a preparation method thereof. The covering agent uses ceramic fiber cloth as a substrate, combines a high-temperature phase-change non-Newtonian material and a silica-alumina sol system, and achieves excellent insulation, oxidation resistance and gap-filling properties through a specific material combination and preparation process. The method includes the preparation and mixing of silica sol and alumina sol, the introduction of an inorganic salt low-melting point eutectic, and the impregnation and multi-layer coating drying of ceramic fiber cloth to form a uniform and seamless insulation layer. The high-temperature phase-change non-Newtonian material has flow-filling properties under high temperature conditions, can automatically fill the gap between the molten steel and the furnace wall and solidify into shape, and ensure the uniformity and high-temperature stability of the covering agent. Compared with traditional powdered covering agents, the invention provides a low-dust, reusable, environmentally friendly and efficient insulation covering agent that is adaptable to metallurgical processes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of steel smelting thermal insulation, and in particular relates to a low-dust thermal insulation covering agent and a preparation method thereof. Background Art

[0002] The tundish plays a connecting role in the continuous casting process. With the increasing requirements for steel quality, the tundish insulation covering agent used to reduce the temperature drop of the molten steel in the tundish, protect the molten steel in the tundish from secondary oxidation, and ensure the smooth pouring of continuous casting has received more and more attention. The functions of the tundish insulation covering agent mainly include the following aspects:

[0003] (1) Prevent crusting on the molten steel surface and provide thermal insulation

[0004] The main function of the tundish insulation covering agent is thermal insulation. If the temperature of the molten steel is too low, it will cause crusting on the liquid surface and freezing of the nozzle, which is mainly caused by the loss of heat energy of the molten steel without the protection of the covering agent. In addition, the higher temperature of the exposed molten steel will cause a bad operating environment for steel workers. Compared with the molten steel without the covering agent, the molten steel with the covering agent can effectively reduce the temperature of the molten steel by 12 to 15°C per furnace. The heat loss of the molten steel in the tundish is small, and the temperature is stable during the pouring process, which is not only easy to control the process, but also conducive to improving the quality of the ingot.

[0005] (2) Absorbing non-metallic inclusions on the molten steel surface

[0006] The time that molten steel stays in the tundish during continuous casting is generally more than 5 minutes. The covering agent on the surface of the molten steel forms a molten layer of appropriate thickness. At this time, the molten covering agent can effectively absorb non-metallic inclusions floating on the surface of the molten steel, as well as floating objects such as refractory particles. In this way, the inclusion content in the molten steel is effectively reduced, providing cleaner molten steel for the crystallizer.

[0007] (3) Prevent secondary oxidation of molten steel

[0008] Analyzing the sources of inclusions in the ingot, it can be found that if there is no isolation and protection of the covering agent, the molten steel is in direct contact with the air, and the inclusions generated by secondary oxidation account for about 35%, and the inclusions caused by the lining of the tundish and the slag are about 55%. With the isolation and protection of the liquid slag layer formed on the surface of the molten steel by the tundish covering agent, the secondary oxidation of the molten steel is effectively reduced and eliminated.

[0009] Most existing thermal insulation covering agents are added by direct spreading, that is, during the metal smelting or casting process, when the molten metal reaches the required temperature and stabilizes, the operator evenly spreads the thermal insulation covering agent on the surface of the molten metal. The covering agent forms a protective film on the surface of the molten metal to prevent heat loss and oxidation of the molten metal. This is the most common method for adding thermal insulation covering agents to the ladle or tundish. Its advantages are simple operation and fast addition speed. The disadvantage is that it is difficult to control the thickness and uniformity of the covering agent, which may result in insufficient thermal insulation effect in some areas.

[0010] The second method is mechanical spraying, which uses special spraying equipment to evenly spray the thermal insulation covering agent on the surface of the molten metal through airflow or mechanical means. The spraying equipment can adjust the amount of covering agent and the spraying speed as needed to ensure uniform coverage and moderate thickness. The advantage is that the covering agent is evenly distributed and suitable for large-scale automated operations. The disadvantage is that the equipment cost is high and maintenance is complicated.

[0011] Therefore, traditional powdered thermal insulation covering agents are no longer suitable for the growing metallurgical industry. It is necessary to develop new forms of thermal insulation covering agents to change the way the thermal insulation covering agents are added and to improve their thermal insulation performance and addition efficiency. Summary of the invention

[0012] In view of the deficiencies in the prior art, the present invention provides a low-dust thermal insulation covering agent and a preparation method thereof. Different from the traditional powdered thermal insulation covering agent, the present invention innovatively produces a reusable cloth-like thermal insulation covering agent, and the corresponding size and thickness can be formulated according to the specific size of the tundish and the thermal insulation requirements. This not only simplifies the addition method of the thermal insulation covering agent, but also ensures the uniformity of the thermal insulation covering agent, and can be recycled and reused, saving costs.

[0013] A method for preparing a low-dust thermal insulation covering agent comprises the following steps:

[0014] (1) Preparation of silica sol: a silicon source and an ethanol aqueous solution are mixed, the pH value is controlled by hydrochloric acid, and a hydrolysis reaction is carried out under stirring to form a silica sol;

[0015] (2) Preparation of aluminum sol: Mix an aluminum source and water, adjust the pH value with hydrochloric acid to form an aluminum sol;

[0016] (3) Mixing silica sol and aluminum sol: mixing silica sol and aluminum sol to obtain silica alumina sol;

[0017] (4) crushing the mullite and sieving it to obtain mullite powder; mixing the mullite powder and silica sol to obtain a high-temperature phase change non-Newtonian material; adding calcium chloride, magnesium chloride, expanded vermiculite powder and fluorite powder to the silica-alumina sol obtained in step (3) and stirring to obtain a covering agent sol;

[0018] (5) Immersing the ceramic fiber cloth in the covering agent sol obtained in step (4) and stirring, then taking it out and drying it to obtain a coated ceramic fiber cloth. According to the thickness requirement, the coated cloth can be stacked in multiple layers to achieve the required thickness;

[0019] (6) The coated ceramic fibers obtained in step (5) are placed at a temperature of 80-120°C for preliminary drying to remove the solvent and gradually shape the sol, and then placed at 400-600°C for curing treatment to ensure that the sol is completely converted into a stable oxide layer, thereby enhancing the mechanical strength and high temperature resistance of the material, and obtaining the low-dust thermal insulation covering agent.

[0020] The silicon source in step (1) is at least one of tetraethoxysilane and sodium silicate.

[0021] The aluminum source in step (2) is at least one of aluminum nitrate and aluminum chloride.

[0022] Preferably, the method for preparing the low-dust thermal insulation covering agent comprises the following steps:

[0023] (1) Preparation of silica sol: 10-20 parts by mass of a silicon source and 80-90 parts by mass of an ethanol aqueous solution are mixed, the pH value is controlled to be between 3 and 4 with hydrochloric acid, and a hydrolysis reaction is carried out under stirring to form a silica sol;

[0024] (2) Preparation of aluminum sol: Mix 10-15 parts of aluminum source and 85-90 parts of water by weight, and adjust the pH value to 2-3 with hydrochloric acid to form aluminum sol;

[0025] (3) Mixing silica-alumina sol: Mix silica sol and alumina sol, wherein the molar ratio of silicon atoms to aluminum atoms is (2-3):1, and stir for 3-5 minutes to obtain silica-alumina sol;

[0026] (4) crushing mullite by weight, passing it through a 100-120 mesh sieve to obtain mullite powder; mixing the mullite powder and silica sol, wherein the mass ratio of the mullite powder to the silica sol is 1:(1-2), to obtain a high-temperature phase-change non-Newtonian material, wherein the viscosity of the high-temperature phase-change non-Newtonian material is in the range of 3000-5000 mPa·s; adding 5-10 parts of calcium chloride, 2-5 parts of magnesium chloride, 3-6 parts of expanded vermiculite powder, and 1-2 parts of fluorite powder to 100 parts of the silica-alumina sol obtained in step (3), stirring for 3-5 minutes, to obtain a covering agent sol;

[0027] (5) Immersing the ceramic fiber cloth in the high-temperature phase change non-Newtonian material obtained in step (4), stirring for 3-5 minutes, then taking it out and drying it at 80-100°C for 6-8 hours to obtain a modified ceramic fiber cloth; then immersing the modified ceramic fiber cloth in the covering agent sol obtained in step (4), stirring for 3-5 minutes, then taking it out and drying it to obtain a coated ceramic fiber cloth. According to the thickness requirements, the coated cloth can be stacked in multiple layers to achieve the required thickness;

[0028] (6) The coated ceramic fibers obtained in step (5) are placed at a temperature of 80-120° C. and dried for 24-48 hours to remove the solvent and gradually shape the sol, and then placed at 400-600° C. for curing treatment for 2-4 hours to ensure that the sol is completely converted into a stable oxide layer, thereby enhancing the mechanical strength and high temperature resistance of the material, and obtaining the low-dust thermal insulation covering agent.

[0029] The concentration of ethanol in the ethanol aqueous solution in step (1) is 20-30wt%.

[0030] The concentration of the hydrochloric acid in step (1) and step (2) is 5-9wt%.

[0031] The silicon source in step (1) is at least one of tetraethoxysilane and sodium silicate.

[0032] The aluminum source in step (2) is at least one of aluminum nitrate and aluminum chloride.

[0033] The silicon source in the silica sol forms a silicon dioxide network structure after hydrolysis and polycondensation reaction. SiO2 is an excellent high temperature resistant material with high strength and chemical stability, providing good mechanical support and thermal insulation performance for the covering agent.

[0034] The aluminum source in the aluminum sol forms aluminum oxide after hydrolysis and polycondensation. Al2O3 has an extremely high melting point and heat resistance, which enhances the thermal shock resistance of the covering agent and has good antioxidant properties.

[0035] Calcium chloride and magnesium chloride: These salts melt at high temperatures and can form a low-melting-point eutectic that helps cover the surface of the molten metal, forming a dense protective layer that prevents oxygen in the air from contacting the molten metal, thereby preventing oxidation. Calcium chloride and magnesium chloride are also hygroscopic and can absorb impurities and moisture in the molten metal, reducing the impact of impurities on the molten metal.

[0036] Vermiculite is a natural mineral with excellent thermal insulation and expansion properties at high temperatures. Expanded vermiculite powder plays a role in heat insulation in the covering agent, while its porous structure helps to absorb impurities in the molten metal and further purify the molten metal.

[0037] As a flux in the covering agent, fluorite powder can reduce the surface tension of the melt at high temperature, promote the fluidity of the covering agent, ensure that it can evenly cover the surface of the molten metal, and enhance the covering effect. At the same time, the presence of fluorite powder can further improve the antioxidant performance of the covering agent.

[0038] Ceramic fiber cloth as a base material has excellent high temperature resistance and mechanical strength. After coating the covering agent sol, it provides support and stability, ensuring that the covering agent maintains a good structure at high temperatures while improving the overall thermal insulation effect of the material.

[0039] High-temperature phase-change non-Newtonian materials exhibit viscoelasticity and fluidity in high-temperature environments, and can automatically fill the gap between the molten steel and the furnace wall to form a continuous and seamless insulation layer to prevent heat loss. Its unique phase-change properties also allow the material to solidify when cooled, improving the stability and durability of the covering agent.

[0040] By mixing silica sol and aluminum sol and adding calcium chloride, magnesium chloride, expanded vermiculite powder and fluorite powder, it is possible to ensure that each component is evenly distributed in the sol. The stirring and impregnation process enables the ceramic fiber cloth to evenly absorb the covering agent sol to form a dense and uniform coating.

[0041] The coated ceramic fiber cloth can be stacked in multiple layers according to actual needs to accurately control the thickness of the covering agent to ensure ideal thermal insulation and protection effects in different application scenarios.

[0042] The drying and curing steps ensure that the covering agent sol is completely converted into a stable oxide layer, which has high mechanical strength and high temperature resistance, can effectively protect the metal liquid and extend the service life of the covering agent.

[0043] Through the synergistic effect of silica sol, aluminum sol, calcium chloride, magnesium chloride, expanded vermiculite powder, fluorite powder and high-temperature phase change non-Newtonian materials, the covering agent is endowed with multiple functions such as thermal insulation, anti-oxidation, impurity adsorption and seamless filling, which effectively improves its protective effect in high-temperature metallurgical processes and provides comprehensive and long-lasting thermal insulation and anti-oxidation protection.

[0044] Beneficial effects of the present invention:

[0045] (1) The present invention introduces a high-temperature phase-change non-Newtonian material based on the traditional ceramic fiber cloth and silica-alumina sol system, which enables it to automatically flow and fill gaps under high temperature conditions, thereby forming a seamless thermal insulation layer, which significantly improves the coverage effect and uniformity in the metallurgical process.

[0046] (2) The low-dust covering agent of the present invention adopts environmentally friendly materials, does not contain organic volatiles, can effectively isolate oxygen at high temperatures, and prevent molten steel from oxidation. The ceramic fiber cloth can be used in multiple layers, and the thickness and density can be adjusted according to process requirements, and is suitable for metallurgical processes of different scales.

[0047] (3) Compared with existing thermal insulation covering agents, this method provides a high-temperature covering agent with higher efficiency and more stable performance through innovative material combination and preparation process, which has broad application prospects in the metallurgical industry. DETAILED DESCRIPTION

[0048] Expanded vermiculite powder and fluorite powder are obtained by crushing and then passing through a 100-mesh sieve.

[0049] Ceramic fiber cloth, item number: 0033, Hejian Jingshun Sealing Material Factory.

[0050] Example 1

[0051] A method for preparing a low-dust thermal insulation covering agent comprises the following steps:

[0052] (1) Preparation of silica sol: 15 parts by weight of a silicon source and 85 parts by weight of an ethanol aqueous solution were mixed, the pH value of which was controlled to 3 with hydrochloric acid, and a hydrolysis reaction was carried out under stirring to form a silica sol;

[0053] (2) Preparation of aluminum sol: 15 parts by weight of an aluminum source and 85 parts by weight of water were mixed, and the pH value was adjusted to 3 with hydrochloric acid to form an aluminum sol;

[0054] (3) Mixing silica sol and aluminum sol, wherein the molar ratio of silicon atoms to aluminum atoms is 2:1, and stirring for 4 minutes to obtain silica alumina sol;

[0055] (4) crushing mullite by weight, passing it through a 100-mesh sieve to obtain mullite powder; mixing the mullite powder and silica sol, wherein the mass ratio of the mullite powder to the silica sol is 1:1.8, to obtain a high-temperature phase-change non-Newtonian material, wherein the viscosity of the high-temperature phase-change non-Newtonian material is 4000 mPa·s; adding 7.5 parts of calcium chloride, 3.5 parts of magnesium chloride, 4 parts of expanded vermiculite powder, and 1.6 parts of fluorite powder to 100 parts of the silica-alumina sol obtained in step (3), stirring for 4 minutes, to obtain a covering agent sol;

[0056] (5) Immersing the ceramic fiber cloth in the high-temperature phase change non-Newtonian material obtained in step (4), stirring for 4 minutes, then taking it out and drying it at 90° C. for 8 hours to obtain a modified ceramic fiber cloth; then immersing the modified ceramic fiber cloth in the covering agent sol obtained in step (4), stirring for 4 minutes, then taking it out and drying it to obtain a coated ceramic fiber cloth. According to the thickness requirements, the coated cloth can be stacked in multiple layers to achieve the required thickness;

[0057] (6) The coated ceramic fibers obtained in step (5) are placed at a temperature of 90° C. for drying for 48 hours, and then placed at 500° C. for curing for 3 hours to obtain the low-dust thermal insulation covering agent.

[0058] The concentration of ethanol in the ethanol aqueous solution in step (1) is 25wt%.

[0059] The concentration of the hydrochloric acid in step (1) and step (2) is 7 wt %.

[0060] The silicon source in step (1) is sodium silicate.

[0061] The aluminum source in step (2) is aluminum chloride.

[0062] Example 2

[0063] A method for preparing a low-dust thermal insulation covering agent comprises the following steps:

[0064] (1) Preparation of silica sol: 15 parts by weight of a silicon source and 85 parts by weight of an ethanol aqueous solution were mixed, the pH value of which was controlled to 3 with hydrochloric acid, and a hydrolysis reaction was carried out under stirring to form a silica sol;

[0065] (2) Preparation of aluminum sol: 15 parts by weight of an aluminum source and 85 parts by weight of water were mixed, and the pH value was adjusted to 3 with hydrochloric acid to form an aluminum sol;

[0066] (3) Mixing silica sol and aluminum sol, wherein the molar ratio of silicon atoms to aluminum atoms is 2:1, and stirring for 4 minutes to obtain silica alumina sol;

[0067] (4) By weight, 7.5 parts of calcium chloride, 3.5 parts of magnesium chloride, 4 parts of expanded vermiculite powder, and 1.6 parts of fluorite powder were mixed and added to 100 parts of the silica-alumina sol obtained in step (3), and stirred for 4 minutes to obtain a covering agent sol;

[0068] (5) Immerse the ceramic fiber cloth in the covering agent sol obtained in step (4), stir for 4 minutes, then take out and dry to obtain the coated ceramic fiber cloth. According to the thickness requirement, the coated cloth can be stacked in multiple layers to achieve the required thickness;

[0069] (6) The coated ceramic fibers obtained in step (5) are placed at a temperature of 90° C. for drying for 48 hours, and then placed at 500° C. for curing for 3 hours to obtain the low-dust thermal insulation covering agent.

[0070] The concentration of ethanol in the ethanol aqueous solution in step (1) is 25wt%.

[0071] The concentration of the hydrochloric acid in step (1) and step (2) is 7 wt %.

[0072] The silicon source in step (1) is sodium silicate.

[0073] The aluminum source in step (2) is aluminum chloride.

[0074] Example 3

[0075] A method for preparing a low-dust thermal insulation covering agent comprises the following steps:

[0076] (1) Preparation of silica sol: 15 parts by weight of a silicon source and 85 parts by weight of an ethanol aqueous solution were mixed, the pH value of which was controlled to 3 with hydrochloric acid, and a hydrolysis reaction was carried out under stirring to form a silica sol;

[0077] (2) By weight, 7.5 parts of calcium chloride, 3.5 parts of magnesium chloride, 4 parts of expanded vermiculite powder, and 1.6 parts of fluorite powder were mixed and added to 100 parts of the silica sol obtained in step (1), and stirred for 4 minutes to obtain a covering agent sol;

[0078] (3) Immersing the ceramic fiber cloth in the covering agent sol obtained in step (2), stirring for 4 minutes, and then taking it out to dry, thereby obtaining a coated ceramic fiber cloth;

[0079] (4) The coated ceramic fibers obtained in step (3) are placed at a temperature of 90° C. for drying for 48 hours, and then placed at 500° C. for curing for 3 hours to obtain the low-dust thermal insulation covering agent.

[0080] The concentration of the hydrochloric acid in step (1) is 7 wt %.

[0081] The concentration of ethanol in the ethanol aqueous solution in step (1) is 25wt%.

[0082] The silicon source in step (1) is sodium silicate.

[0083] Example 4

[0084] A method for preparing a low-dust thermal insulation covering agent comprises the following steps:

[0085] (1) Preparation of aluminum sol: 15 parts by weight of an aluminum source and 85 parts by weight of water were mixed, and the pH value was adjusted to 3 with hydrochloric acid to form an aluminum sol;

[0086] (2) By weight, 7.5 parts of calcium chloride, 3.5 parts of magnesium chloride, 4 parts of expanded vermiculite powder, and 1.6 parts of fluorite powder were mixed and added to 100 parts of the aluminum sol obtained in step (1), and stirred for 4 minutes to obtain a covering agent sol;

[0087] (3) Immersing the ceramic fiber cloth in the covering agent sol obtained in step (2), stirring for 4 minutes, and then taking it out to dry, thereby obtaining a coated ceramic fiber cloth;

[0088] (4) The coated ceramic fibers obtained in step (3) are placed at a temperature of 90° C. for drying for 48 hours, and then placed at 500° C. for curing for 3 hours to obtain the low-dust thermal insulation covering agent.

[0089] The concentration of the hydrochloric acid in step (1) is 7 wt %.

[0090] The aluminum source in step (1) is aluminum chloride.

[0091] Example 5

[0092] A method for preparing a low-dust thermal insulation covering agent comprises the following steps:

[0093] (1) Preparation of silica sol: 15 parts by weight of a silicon source and 85 parts by weight of an ethanol aqueous solution were mixed, the pH value of which was controlled to 3 with hydrochloric acid, and a hydrolysis reaction was carried out under stirring to form a silica sol;

[0094] (2) Preparation of aluminum sol: 15 parts by weight of an aluminum source and 85 parts by weight of water were mixed, and the pH value was adjusted to 3 with hydrochloric acid to form an aluminum sol;

[0095] (3) Mixing silica sol and aluminum sol: Mix silica sol and aluminum sol, wherein the molar ratio of silicon atoms to aluminum atoms is 4:1, and stir for 4 minutes to obtain silica alumina sol;

[0096] (4) By weight, 7.5 parts of calcium chloride, 3.5 parts of magnesium chloride, 4 parts of expanded vermiculite powder, and 1.6 parts of fluorite powder were mixed and added to 100 parts of the silica-alumina sol obtained in step (3), and stirred for 4 minutes to obtain a covering agent sol;

[0097] (5) Immerse the ceramic fiber cloth in the covering agent sol obtained in step (4), stir for 4 minutes, and then take out and dry to obtain the coated ceramic fiber cloth;

[0098] (6) The coated ceramic fibers obtained in step (5) are placed at a temperature of 90° C. for drying for 48 hours, and then placed at 500° C. for curing for 3 hours to obtain the low-dust thermal insulation covering agent.

[0099] The concentration of ethanol in the ethanol aqueous solution in step (1) is 25wt%.

[0100] The concentration of the hydrochloric acid in step (1) and step (2) is 7 wt %.

[0101] The silicon source in step (1) is sodium silicate.

[0102] The aluminum source in step (2) is aluminum chloride.

[0103] Example 6

[0104] A method for preparing a low-dust thermal insulation covering agent comprises the following steps:

[0105] (1) Preparation of silica sol: 15 parts by weight of a silicon source and 85 parts by weight of an ethanol aqueous solution were mixed, the pH value of which was controlled to 3 with hydrochloric acid, and a hydrolysis reaction was carried out under stirring to form a silica sol;

[0106] (2) Preparation of aluminum sol: 15 parts by weight of an aluminum source and 85 parts by weight of water were mixed, and the pH value was adjusted to 3 with hydrochloric acid to form an aluminum sol;

[0107] (3) Mixing silica-alumina sol: Mix silica sol and alumina sol, wherein the molar ratio of silicon atoms to aluminum atoms is 1:1, and stir for 4 minutes to obtain silica-alumina sol;

[0108] (4) By weight, 7.5 parts of calcium chloride, 3.5 parts of magnesium chloride, 4 parts of expanded vermiculite powder, and 1.6 parts of fluorite powder were mixed and added to 100 parts of the silica-alumina sol obtained in step (3), and stirred for 4 minutes to obtain a covering agent sol;

[0109] (5) Immerse the ceramic fiber cloth in the covering agent sol obtained in step (4), stir for 4 minutes, and then take out and dry to obtain the coated ceramic fiber cloth;

[0110] (6) The coated ceramic fibers obtained in step (5) are placed at a temperature of 90° C. for drying for 48 hours, and then placed at 500° C. for curing for 3 hours to obtain the low-dust thermal insulation covering agent.

[0111] The concentration of ethanol in the ethanol aqueous solution in step (1) is 25wt%.

[0112] The concentration of the hydrochloric acid in step (1) and step (2) is 7 wt %.

[0113] The silicon source in step (1) is sodium silicate.

[0114] The aluminum source in step (2) is aluminum chloride.

[0115] Comparative Example 1

[0116] A method for preparing a low-dust thermal insulation covering agent comprises the following steps:

[0117] (1) Preparation of silica sol: 15 parts by weight of a silicon source and 85 parts by weight of an ethanol aqueous solution were mixed, the pH value of which was controlled to 3 with hydrochloric acid, and a hydrolysis reaction was carried out under stirring to form a silica sol;

[0118] (2) Preparation of aluminum sol: 15 parts by weight of an aluminum source and 85 parts by weight of water were mixed, and the pH value was adjusted to 3 with hydrochloric acid to form an aluminum sol;

[0119] (3) Mixing silica sol and aluminum sol, wherein the molar ratio of silicon atoms to aluminum atoms is 2:1, and stirring for 4 minutes to obtain silica alumina sol;

[0120] (4) By weight, 7.5 parts of calcium chloride, 3.5 parts of magnesium chloride, 4 parts of expanded vermiculite powder, and 1.6 parts of fluorite powder were mixed and added to 100 parts of the silica-alumina sol obtained in step (3), and stirred for 4 minutes to obtain a covering agent sol;

[0121] (5) The covering agent sol obtained in step (4) is dried at 90° C. for 48 hours, then cured at 500° C. for 3 hours, and crushed through a 100-mesh sieve to obtain the low-dust thermal insulation covering agent.

[0122] The concentration of ethanol in the ethanol aqueous solution in step (1) is 25wt%.

[0123] The concentration of the hydrochloric acid in step (1) and step (2) is 7 wt %.

[0124] The silicon source in step (1) is sodium silicate.

[0125] The aluminum source in step (2) is aluminum chloride.

[0126] Comparative Example 2

[0127] A method for preparing a low-dust thermal insulation covering agent comprises the following steps:

[0128] (1) Preparation of silica sol: 15 parts by weight of a silicon source and 85 parts by weight of an ethanol aqueous solution were mixed, the pH value of which was controlled to 3 with hydrochloric acid, and a hydrolysis reaction was carried out under stirring to form a silica sol;

[0129] (2) Preparation of aluminum sol: 15 parts by weight of an aluminum source and 85 parts by weight of water were mixed, and the pH value was adjusted to 3 with hydrochloric acid to form an aluminum sol;

[0130] (3) Mixing silica sol and aluminum sol, wherein the molar ratio of silicon atoms to aluminum atoms is 2:1, and stirring for 4 minutes to obtain silica alumina sol;

[0131] (4) Immerse the ceramic fiber cloth in the silica-alumina sol obtained in step (3), stir for 4 minutes, then take out and dry to obtain a coated ceramic fiber cloth;

[0132] (5) The coated ceramic fibers obtained in step (4) are placed at a temperature of 90° C. for drying for 48 hours, and then placed at 500° C. for curing for 3 hours to obtain the low-dust thermal insulation covering agent.

[0133] The concentration of ethanol in the ethanol aqueous solution in step (1) is 25wt%.

[0134] The concentration of the hydrochloric acid in step (1) and step (2) is 7 wt %.

[0135] The silicon source in step (1) is sodium silicate.

[0136] The aluminum source in step (2) is aluminum chloride.

[0137] Comparative Example 3

[0138] The refined thermal insulation covering agent disclosed in Example 1 of CN102618694B comprises the following raw materials in parts by weight: 35 parts of rice husk ash, 28 parts of silicon dioxide, 3 parts of magnesium oxide, 5 parts of attapulgite, 4 parts of calcium oxide, 13 parts of aluminum oxide, 3 parts of fluorite, 8 parts of expanded vermiculite and 5 parts of carbon black.

[0139] The preparation method of the refined thermal insulation covering agent comprises the following steps: weighing each raw material according to its weight, then mixing and stirring for 30-40 minutes, processing industrial starch and water into balls, and drying to obtain the finished product.

[0140] Test Example 1

[0141] The thermal insulation performance of the thermal insulation covering agent prepared in the embodiment and the comparative example was tested. The thermal insulation performance test was carried out using a one-way furnace; the heating elements of the one-way heating furnace were 6 silicon carbon rods, the operating temperature could reach 1450°C, and a silicon carbon soaking plate was laid on top; the thermal insulation layer used Al2O3 foam bricks with high refractoriness and good thermal insulation performance.

[0142] The one-way heating furnace controls the voltage and current changes of the input furnace through the DWK-702 precision temperature controller, so that the bottom couple is maintained at a certain temperature to keep the temperature in the furnace constant. When different covering agents are added to the silicon-carbon soaking plate, the heat dissipation of the one-way heating furnace changes due to different thermal insulation properties. The covering agent with poor thermal insulation performance has a higher surface temperature, and the furnace dissipates heat quickly to the environment. The power input to the furnace by the temperature controller is large, and vice versa. Therefore, at the same temperature and the same thickness, the thermal insulation performance of the covering agent can be judged according to the change of the surface temperature of the covering agent over time. The temperature of the molten steel in the tundish is about 1550℃, and the covering agent spreads on the surface of the molten steel to form a molten layer, a sintered layer and a powdery layer. The boundary temperature of the powdery layer and the sintered layer is generally about 800℃, so the experiment uses a constant temperature of 800℃ to simulate the temperature change of the sintered layer of the covering agent.

[0143] The surface of the silicon-carbon soaking plate was evenly paved with 5 mm thick thermal insulation covering agents prepared in various embodiments and comparative examples, and the surface temperature of the thermal insulation covering agents was measured after 10 minutes.

[0144] The results are shown in Table 1

[0145] Table 1: Surface temperature of thermal insulation covering agent

[0146]

[0147] Test Example 2

[0148] Field tests were conducted on a billet continuous casting machine, with SS400 as the casting steel, 38t of tundish capacity, 1520-1540°C of molten steel in the tundish, and 20mm thick thermal insulation covering agents prepared in various embodiments and comparative examples were laid or sprayed. During each furnace casting, the temperature of the molten steel in the tundish was measured, the temperature change was recorded, and the temperature drop value was calculated. Five temperature drop values ​​were obtained for each covering agent, and the average value was taken.

[0149] The results are shown in Table 2

[0150] Table 2: Temperature drop of molten steel in tundish

[0151]

[0152] It can be seen from the test results of Table 1 and Table 2 that the thermal insulation covering agent prepared in Example 1 has the best thermal insulation performance. The main difference between Example 1 and Example 2 is the application of high-temperature phase change non-Newtonian material. Example 1 uses a high-temperature phase change non-Newtonian material, which can automatically fill the tiny gap between the covering agent and the surface of the molten steel under high temperature conditions to form a seamless, dense insulation layer, significantly reducing heat loss, and quickly solidifying after cooling, thereby improving the stability of the covering agent and the long-term thermal insulation effect. Compared with Example 2 in which no high-temperature phase change non-Newtonian material is added, the thermal insulation performance of Example 1 is significantly better.

[0153] Example 3 uses a single silica sol, and Example 4 uses a single aluminum sol. Their thermal insulation performance is lower than that of Example 2. Adjusting the ratio of silica-alumina sol in Example 5 and Example 6 also leads to a decrease in their thermal insulation performance. This shows that silica-alumina sol can better play a role in heat insulation when matched in a certain ratio. The silicon source in the silica sol forms a silicon dioxide network structure after hydrolysis and polycondensation. SiO2 is an excellent high-temperature resistant material with high strength and chemical stability, which provides good mechanical support and thermal insulation performance for the covering agent. The aluminum source in the aluminum sol forms aluminum oxide after hydrolysis and polycondensation. Alumina has an extremely high melting point and heat resistance, which enhances the thermal shock resistance of the covering agent, and has good antioxidant properties. The combination of the two can form a better thermal insulation structure.

[0154] Comparative Example 1 does not use ceramic fiber cloth as a carrier, and directly pulverizes the sol after drying to obtain a traditional form of thermal insulation covering agent, which not only has a larger dosage, but also has a thermal insulation effect far less than Example 1, which also shows that the use of ceramic fiber cloth as a substrate, coupled with a sol system composed of inorganic materials, can effectively improve the thermal insulation performance of the covering agent. The present invention believes that this is because the coated ceramic fiber cloth can maintain good stability and mechanical strength under high temperature conditions, so that the covering agent is distributed more evenly, and is not easy to fall off or decompose, providing long-term high temperature protection. Comparative Example 2 does not add traditional thermal insulation covering agent components such as calcium chloride, magnesium chloride, expanded vermiculite powder, and fluorite powder, and its thermal insulation effect is the worst, which shows that the thermal insulation ability of the ceramic fiber cloth coated with aerogel itself is poor, and only when combined with traditional thermal insulation covering agents such as calcium chloride, magnesium chloride, expanded vermiculite powder, and fluorite powder, it has an excellent thermal insulation effect. The comparison of Example 1 and Comparative Example 3 shows that the thermal insulation covering agent prepared by the present invention is more outstanding than the existing thermal insulation covering agent.

[0155] In summary, Example 1, through the synergistic effect of silica sol, aluminum sol, calcium chloride, magnesium chloride, expanded vermiculite powder, fluorite powder and high-temperature phase change non-Newtonian materials, gives the covering agent multiple functions such as thermal insulation, anti-oxidation, impurity adsorption and seamless filling, effectively improving its protective effect in high-temperature metallurgical processes, providing comprehensive and long-lasting thermal insulation and anti-oxidation protection, and showing more excellent thermal insulation performance compared with other embodiments and comparative examples.

Claims

1. A method for preparing a low-dust thermal insulation covering agent, characterized in that: The following steps are involved: (1) Preparing silica sol: by weight, 10-20 parts of a silicon source and 80-90 parts of an ethanol aqueous solution are mixed, the pH value is controlled to be between 3 and 4 with hydrochloric acid, and a hydrolysis reaction is carried out under stirring to form a silica sol; the silicon source is at least one of tetraethoxysilane and sodium silicate; the concentration of ethanol in the ethanol aqueous solution is 20-30wt%; the concentration of the hydrochloric acid is 5-9wt%; (2) Preparing aluminum sol: by weight, 10-15 parts of an aluminum source and 85-90 parts of water are mixed, and the pH value is adjusted to 2-3 with hydrochloric acid to form an aluminum sol; the aluminum source is at least one of aluminum nitrate and aluminum chloride; the concentration of the hydrochloric acid is 5-9wt%; (3) Preparation of silica-alumina sol: Mix silica sol and alumina sol, wherein the molar ratio of silicon atoms to aluminum atoms is (2-3):1, and stir for 3-5 minutes to obtain silica-alumina sol; (4) Preparing a high-temperature phase-change non-Newtonian material and a covering agent sol: crushing mullite by weight, passing it through a 100-120 mesh sieve to obtain mullite powder; mixing the mullite powder and silica sol, wherein the mass ratio of the mullite powder to the silica sol is 1:(1-2), to obtain a high-temperature phase-change non-Newtonian material, wherein the viscosity of the high-temperature phase-change non-Newtonian material is in the range of 3000-5000 mPa·s; adding 5-10 parts of calcium chloride, 2-5 parts of magnesium chloride, 3-6 parts of expanded vermiculite powder, and 1-2 parts of fluorite powder to 100 parts of the silica-alumina sol obtained in step (3), stirring for 3-5 minutes, to obtain a covering agent sol; (5) Ceramic fiber cloth treatment: immerse the ceramic fiber cloth in the high-temperature phase change non-Newtonian material obtained in step (4), stir for 3-5 minutes, then take out and dry at 80-100°C for 6-8 hours to obtain a modified ceramic fiber cloth; then immerse the modified ceramic fiber cloth in the covering agent sol obtained in step (4), stir for 3-5 minutes, then take out and dry to obtain a coated ceramic fiber cloth; (6) The coated ceramic fibers obtained in step (5) are placed at a temperature of 80-120° C. and dried for 24-48 hours to remove the solvent, so that the sol is gradually formed, and then placed at 400-600° C. for curing treatment for 2-4 hours to obtain the low-dust thermal insulation covering agent.

2. A low-dust thermal insulation covering agent, characterized in that: The low-dust thermal insulation covering agent is prepared by the preparation method of claim 1.

Citation Information

Patent Citations

  • Refining heat insulation covering agent and preparation method thereof

    CN102618694B

  • Sol-coated slag remover as well as preparation method and application thereof

    CN115488293A

  • High-temperature-resistant thermal insulation coating and preparation method thereof

    CN116535886A

  • Lightweight dry refractory

    US6458732B1